Semiconducting single-walled carbon nanotubes synthesized by S-doping - Li, Zijiong; Wang, L.; Su, Yanjie; Liu, Ping; Zhang, Yafei (Nano-Micro Letters, 2009)
An approach was presented for synthesis of semiconducting single-walled carbon nanotubes (SWNTs) by sulfur (S) doping with the method of graphite arc discharge. Raman spectroscopy, UV-vis-NIR absorption spectroscopy and electronic properties measurements indicated the semconducting properties of the SWNTs samples. Simulant calculation indicated that S doping could induce convertion of metallic SWNTs into semiconducting ones. This strategy may pave a way for the direct synthesis of pure semiconducting SWNTs.